Kulturowe uwarunkowania innowacyjności przedsiębiorstw we współczesnym świecie biznesu - Stańczyk, Sylwia (Cultural Way to Innovation in a Contemporary Business World, 2006)
The purpose of this paper is to answer the questions: how create an innovative organizational culture and what attributes are typical for that Culture as a condition of companies innovation in a contemporary business world.Showed issues, considerations and conclusions in this paper, are made in support of literature studies results of an empirical researches and author's own experience.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 160-166